A new stygobiont species of Halocaridinides Fujino & Shokita, 1975 (Crustacea, Decapoda, Caridea, Atyidae) from caves on Socotra Island (Yemen), with notes on the genus - Fransen, Charles H.j.m.; Damme, K. Van (Zootaxa, 2018)
We describe a new species of stygobiont atyid shrimp of the genus Halocaridinides Fujino & Shokita, 1975 from subterranean brackish and freshwater environments on Socotra Island (Yemen). This is the first atyid shrimp discovered in the Socotra Archipelago. This Socotran endemic is the second species of Halocaridinides recorded from an Indian Ocean island and the first to occur in non-anchialine environments. The new species is characterized by the absence of eye pigmentation, a reduced rostrum and the presence of a single spine in the uropodal exopod diaeresis. Morphological variability in the robustness of the first and the second chelipeds, particularly obvious in the chelae, may indicate local speciation or phenotypical plasticity. At both extremes of the variation, animals with most slender (tenuis type) or robust (robustus type) morphologies occur. We discuss the Indo-Pacific distribution of the genus and the potential origin of the new Socotran species. An amended diagnosis for the genus and a key to all species are included.